Clinical and advanced neurophysiology in the prognostic and diagnostic evaluation of disorders of consciousness: review of an IFCN-endorsed expert group. Issue 11 (November 2020) - Comanducci, A.; Boly, M.; Claassen, J.; De Lucia, M.; Gibson, R.M.; Juan, E.; Laureys, S.; Naccache, L.; Owen, A.M.; Rosanova, M.; Rossetti, A.O.; Schnakers, C.; et al.
Highlights: We provide an overview of EEG-based techniques in the prognostic and diagnostic assessment of DoC. We highlight bridging principles between conventional and investigational approaches. We share expert opinions and considerations on the technical and conceptual caveats. Abstract: The analysis of spontaneous EEG activity and evoked potentials is a cornerstone of the instrumental evaluation of patients with disorders of consciousness (DoC). The past few years have witnessed an unprecedented surge in EEG-related research applied to the prediction and detection of recovery of consciousness after severe brain injury,  opening up the prospect that new concepts and tools may be available at the bedside. This paper provides a comprehensive, critical overview of both consolidated and investigational electrophysiological techniques for the prognostic and diagnostic assessment of DoC. We describe conventional clinical EEG approaches, then focus on evoked and event-related potentials, and finally we analyze the potential of novel research findings. In doing so, we (i) draw a distinction between acute, prolonged and chronic phases of DoC, (ii) attempt to relate both clinical and research findings to the underlying neuronal processes and (iii) discuss technical and conceptual caveats. The primary aim of this narrative review is to bridge the gap between standard and emerging electrophysiological measures for the detection and prediction of recovery of consciousness. The ultimate scope is to provide a reference and common ground for academic researchers active in the field of neurophysiology and clinicians engaged in intensive care unit and rehabilitation.